Keunikan Hukum Waris Adat Minangkabau - Adelia, Indah; Wahyuni, Sri; Tarigan, Tetty Marlina (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The culture of the Minangkabau people is matrilineal, with property and land being passed on from mothers to daughters, while religious and political affairs are the affairs of the men (although half of the women play a role. In this study, a literature review research method was used, where the literature review research is the result of analyzing various conceptual information as well as qualitative and quantitative data from various previously published scientific articles.This research results that the application of Minangkabau customary law of the Chaniago Kenagarian Guguak Koto VIII tribe, is related to the problem of inheritance over land using a matrilineal system. regarding the system for dividing inheritance over this land which is an inheritance to the Chaniago tribe, where since ancient times, inheritance may not be sold. Keywords: Culture, Inheritance, Minangkabau Society